(untitled) (Research, Society and Development, 2021)
Objective: This study sought to understand the participation of the Mental Health Council in the policy of the Psychosocial Care Network according to the view of health professionals. Method: This is an Integrative Review that allows the search and critical analysis of scientific production related to the research theme, where the six steps of Mendes, Silveira and Galvão and the PCC strategy (P=Population, C=Concept, C=Context) were followed. Results and discussions: Among the selected articles, the main results obtained relate to two main points: (1) gap between policy and practice; and (2) the lack of knowledge/unpreparedness of professionals in the mental health field. And for a more complete discussion, a third point was addressed: (3) the impact of the pandemic on mental health services. Final considerations: Although most studies fit according to the guidelines of the National Mental Health Policy, many strategies still bear roots of the biomedical model.